Peer-to-peer insights from young ACP agripreneurs - Afari-Kwarteng, Jemima; Kabamba, Alpha; Kirwin, Litia (Technical Centre for Agricultural and Rural Cooperation, 2019)
Springboard (Nigeria) trains young farmers in organic farming, production and processing of crops specifically plantain and maize